Caracterização da Região Metropolitana de Ribeirão Preto SP - Melo, Lívia Mara de Almeida (2024)
Brazil had a relevant and extensive territorial organization, made up of 82 metropolitan regions that were determined for specific treatment purposes depending on the particularities of each region. Although most of the criteria can still be considered pertinent, some points must be highlighted: it is clear that industry performance plays an important role in the metropolization process of these regions, as does migration, responsible for the sudden population growth. In the context of third modernity, and in countries with a recent industrialization process, such as Brazil, these criteria become more decisive, because of the industry, although important, has not been the driving sector of the urban economy for a long time, having been surpassed by the tertiary. The challenges faced by metropolises have a national impact, as they concentrate the majority of corporations and services of interest to the Union, configuring a center for investment and capital accumulation, making cooperation between municipal, state and, mainly federal, public authorities important in the debate of these issues. The objective of the research was to characterize the Metropolitan Region of Ribeirão Preto, based on the historical and spatial process. Initially, data and supporting aspects of this study were collected and analyzed, with regard to the historical process of creation of metropolitan regions, and consequently the Ribeirão Preto Metropolitan Region.